Learning disability screening: impact on prison programmes. Issue 3 (4th May 2020) - Ramsay, Laura; Wakeling, Helen; De Lucchi, Rebecca; Gilbert, Hannah
Abstract : Purpose: The purpose of this paper is to examine staff views' of the usefulness of the Her Majesty's Prison and Probation Service (HMPPS) screening tools for learning disability and/or learning challenges (LDC) on offending behaviour programme selection and programme participant's learning experiences. Design/methodology/approach: In total, 11 treatment managers (TMs) and 10 programme graduates across 4 prison sites, from a range of HMPPS accredited programmes were interviewed. The interviews were transcribed, analysed and interpreted using Braun and Clarke's (2006) method of thematic analysis. Findings: Overall, TMs found the screening tools useful in aiding programme allocation decisions, particularly, in terms of the triangulated approach and were, in general, using them in line with the guidance. A number of key factors influenced programme allocation decisions, including participant factors, information gathered from a number of sources and from a range of staff and in collaboration with the individual. The importance of being responsive to the needs of the individual was highlighted. Group participants generally felt they were on the right programme according to their needs and found the programmes responsive. Suggestions for further research and improving programme selection are made. Research limitations/implications: Data were collected from four prisons, each providing a number of different accredited programmes. Caution is, therefore, needed when generalising the findings. Originality/value: This research contributes to ensuring that those with LDC have equality of opportunity in reducing their risk of reoffending through accessing HMPPS accredited offending behaviour programmes most responsive to their learning needs. It also contributes to the growing evidence base about the effective use of LDC screening tools in forensic settings.